Organising care and community in the era of the 'gay disease': Gay community responses to HIV/AIDS and the production of differentiated care geographies in Vancouver. (May 2021) - Catungal, John Paul; Klassen, Benjamin; Ablenas, Robert; Lambert, Sandy; Chown, Sarah; Lachowsky, Nathan
Scholarship on the place of the HIV/AIDS crisis in urban geographies of sexual minority activism has powerfully insisted on the importance of community organising as a response to state and societal failures and to their homophobic, AIDS phobic and morally conservative underpinnings. This paper extends this scholarship by examining the urban social geographies of exclusion produced by such community organising efforts. It draws on the perspectives of long-term survivors of HIV/AIDS (LTS) in Vancouver to highlight the differentiated care geographies of HIV/AIDS that resulted from the racialised, classed and gendered politics and urban imaginations enacted by gay and allied HIV/AIDS organising. Though LTS networks, spaces and politics of care and community were more extended than Vancouver's gay community during the 1980s and 1990s, the centring of the West End gay village in many community-led responses to HIV/AIDS resulted in LTS geographies outside the West End being excluded from important systems of care and community. LTS narratives of the city at the time of the 'gay disease' thus tell an urban politics of sexual and health activisms as shaped not only by processes of heteronormativity and homophobia but also of racially, colonially and class-inflected homonormative urban imaginaries.